Economic and environmental assessment of succinic acid production from sugarcane bagasse - Shaji, Arun; Shastri, Yogendra; Kumar, Vinod; Ranade, Vivek V.; Hindle, Neil (American Chemical Society, 2021)
This work presents technoeconomic analysis (TEA) and life cycle assessment (LCA) of a novel biorefinery producing succinic acid (SA) from sugarcane bagasse. The process consists of acid pretreatment, fermentation, followed by downstream separation and purification. Experimental data for pretreatment and fermentation are adapted for a plant processing 4 t/h of dry bagasse, producing 405 kg/h of succinic acid with the same quantity of acetic acid as a side product. Downstream separation is simulated in ASPEN PLUS. The facility is assumed to be annexed to and heat-integrated with an existing sugar mill in India. LCA is performed considering cradle-to-gate scope with 1 kg of SA as the functional unit. The TEA results show that although the process is currently not economically feasible, expected improvements in fermentation yields will make it cost-competitive. For the expected yield, the product cost of SA is INR 121/kg ($1.61/kg), and the selling price of succinic acid should be INR 178/kg ($2.37/kg) for a payback period of 4 years. Pretreatment and fermentation are the biggest contributors to the product cost. The life cycle greenhouse gas (GHG) emissions are 1.39 kg of CO2 equiv/kg succinic acid with electricity as the major contributor. Process improvement opportunities are identified to reduce the costs, as well as life cycle impacts.
Keywords: succinic acid; bagasse; xylose; product cost; GHG emissions